Adam Mickiewicz’s youth under a foreign roof: in Novogrudok, Vilnius, Kaunas, in the Empire - Pusz, Wiesław (Prace Polonistyczne, 2023)
The article offers a list of validated and reconstructed “addresses” of places where Mickiewicz stayed in his youth (until 1829) and discusses them in specific contexts. The changing places of residence were the result of constant movement of variable genesis and course. These relocations affected the life of Mickiewicz as a high school student, a university student, and a displaced individual. They happened in different circumstances and involved taking various routes. Some of them were of Mickiewicz’s own accord: due to familial, sentimental, and collegial reasons, or as a result of official duties imposed by the tsar’s decrees. Most relocations took place in Lithuania. The less numerous, albeit significantly longer, official journeys of hundreds of kilometers were made by Mickiewicz in Russia. These relocations are presented in the form of calculations and location lists.